2009
DOI: 10.1007/dcr.0b013e31819acb99
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Mutation in Mitochondrial DNA Displacement Loop Region in Human Colorectal Cancer

Abstract: Mutations in mtDNA D-loop region probably do not cause colorectal cancer but are more likely to be epiphenomena; patients with the high mtDNA variants are at a higher risk of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 18 publications
4
28
0
Order By: Relevance
“…This was significantly decreased to 2 and 10 in the normal group (Table 2). Previous investigations have shown a high rate of mutations in D-loop region in some cancers such as colorectal or gastric cancers [21,22]; some of these mutations are associated with special community haplogroups. Therefore, it could be concluded that D-loop mutations disrupt apoptosis in two direction; they can either cause an uncontrolled cell proliferation (cancers) and arrest or a decreased cell proliferation (degenerative disorders or growth arrest in fetus).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This was significantly decreased to 2 and 10 in the normal group (Table 2). Previous investigations have shown a high rate of mutations in D-loop region in some cancers such as colorectal or gastric cancers [21,22]; some of these mutations are associated with special community haplogroups. Therefore, it could be concluded that D-loop mutations disrupt apoptosis in two direction; they can either cause an uncontrolled cell proliferation (cancers) and arrest or a decreased cell proliferation (degenerative disorders or growth arrest in fetus).…”
Section: Discussionmentioning
confidence: 98%
“…D-loop has been demonstrated as a mutation 'hot spot' in some disorders such as cancers. The rate of mutations in D-loop is much higher than in other parts of mtDNA, and such alterations can affect the transcription or translation of mtDNA [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damage to and somatic mutations of mtDNA may lead to impairment of the OXPHOS system and increased ROS production, which subsequently enhances the rate of DNA mutations (8). Numerous researchers have reported that mtDNA mutations or polymorphisms, particularly in the D-loop region, were detected in different types of cancer, including human colorectal (9), ovarian (10) and thyroid (11) cancer, in addition to HCC (12). Furthermore, the association between mtDNA polymorphisms or mutations and the prognoses of cancer has also been investigated, but the results have been ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…[10] D-loop mutations have been detected in a wide variety of cancers. [11][12][13][14][15] In particular, the D310 mononucleotide repeat within the D-loop is a hotspot for somatic mutations in colorectal, [16] gastric, [17] lung, [18] and thyroid tumors. [19] Mutations in the D514 region have been associated with thyroid tumors.…”
Section: Introductionmentioning
confidence: 99%